Novel photolytic cross-linking agent as well as preparation method and application thereof
By synthesizing a novel photolytic crosslinking agent Cou-AA, the problems of short absorption peaks and low photolysis efficiency of existing crosslinking agents are solved, and efficient photolysis under 250-350nm light excitation is achieved, which is applicable to fields such as photolithography, photopatterning, microfluidic chip manufacturing and cell bioengineering.
Patent Information
- Application Number
- CN202511107374.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-11-25
AI Technical Summary
Existing photolytic crosslinking agents have short absorption peak wavelengths, low photolysis efficiency, and high bio-phototoxicity, resulting in long exposure times and shallow penetration depths, making it difficult to meet the application requirements of fields such as photolithography, photopatterning, microfluidic chip manufacturing, and cell bioengineering.
A novel photodegradable crosslinking agent, Cou-AA, was synthesized through a series of chemical reactions using 4-bromo-m-diphenol and ethyl 4-chloroacetoacetate as starting materials. It was then polymerized with acrylic acid and ammonium persulfate under specific conditions to form a photodegradable gel, and the collapse of the crosslinking network was achieved by excitation with 250-350 nm light.
The novel photolytic crosslinking agent exhibits strong absorption at 250-350 nm and high photolysis efficiency, making it suitable for large-scale production. It has broad application prospects in fields such as photolithography, photopatterning, microfluidic chip manufacturing, and cell bioengineering.
Smart Images

Figure CN121005672A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photofunctional materials technology, specifically relating to a novel photodegradable crosslinking agent, its preparation method, and its application. Background Technology
[0002] Photodegradable gel materials can collapse their internal cross-linked networks under light excitation at specific wavelengths, showing great promise for applications in photolithography, photopatterning, microfluidic chip manufacturing, cell bioengineering, and controlled drug release. Photodegradable gels are generally prepared by the free radical polymerization of photodegradable cross-linking agents with other monomers to form a three-dimensional cross-linked network. Light excitation causes bond breaking in the cross-linking agent, leading to the collapse of the three-dimensional cross-linked network and thus achieving photodegradation. Therefore, photodegradable cross-linking agents are key to enabling gels to possess photodegradable properties.
[0003] Currently, photolytic crosslinking agents generally use o-nitrobenzyl and its derivatives as photolytic responsive groups. Their absorption peak wavelengths are often shorter than 280 nm, and their photolysis efficiency is low, resulting in drawbacks such as long exposure times, high bio-phototoxicity, and shallow penetration depth. Therefore, this paper proposes a novel photolytic crosslinking agent, its preparation method, and its applications. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a novel photodegradable crosslinking agent, its preparation method, and its application, thereby solving the problems in the prior art.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A photodegradable crosslinking agent, with the following structural formula:
[0007]
[0008] The above-mentioned method for preparing a photodegradable crosslinking agent includes the following steps:
[0009] S1, ethyl 4-chloroacetoacetate was added to methanesulfonic acid containing 4-bromo-m-diphenol, and after stirring, the reaction solution was cooled, allowed to stand to precipitate, filtered to obtain a solid, and then washed and dried to obtain compound 1;
[0010] S2, compound 1, K2CO3 and acrylic acid were dissolved in DMF, heated to react, then cooled to room temperature, and after extraction, drying, rotary evaporation and purification, compound 2 was obtained;
[0011] S3, under a nitrogen atmosphere, triethylamine and acryloyl chloride are added sequentially to an ultra-dry THF solution containing compound 2 to carry out the reaction; after the reaction is completed, the solvent is evaporated and purified to obtain the photolytic crosslinking agent.
[0012] Furthermore, the synthetic route for the photodegradable crosslinking agent is as follows:
[0013]
[0014] Furthermore, the heating reaction is carried out under anhydrous and oxygen-free conditions.
[0015] The above-mentioned photodegradable crosslinking agent is used in the preparation of photodegradable gels.
[0016] A method for preparing a photolyzable gel includes the following steps:
[0017] Acrylic acid, the above-mentioned photodegradable crosslinking agent and ammonium persulfate were dissolved in dimethyl sulfoxide and mixed evenly to obtain a pregel solution;
[0018] After polymerizing the pregel solution, it is immersed in methanol to obtain a photodegradable gel.
[0019] Furthermore, the mass ratio of acrylic acid, photodegradable crosslinking agent, and ammonium persulfate is 133:4:2.
[0020] Furthermore, the polymerization temperature is 73°C.
[0021] A photolyzable gel was prepared using the method described above.
[0022] The above-mentioned photolyzable gels are used in the preparation of microfluidic chips and drug carriers.
[0023] The beneficial effects of this invention are:
[0024] (1) The novel photolytic crosslinking agent prepared by the present invention has strong absorption at 250-350nm. Compared with traditional crosslinking agents based on o-nitrobenzyl and its derivatives, it has the advantages of longer absorption wavelength and higher photolysis efficiency.
[0025] (2) The novel photodegradable crosslinking agent prepared by the present invention can undergo free radical polymerization reaction with monomers containing olefin bonds to form a gel with a three-dimensional crosslinked network structure. The gel can undergo photodegradation under light excitation of 250nm to 350nm and has broad application prospects in photolithography, photopatterning, microfluidic chip manufacturing, cell bioengineering, and controlled drug release.
[0026] (3) The novel photodegradable crosslinking agent prepared by the present invention has the advantages of simple synthesis and readily available raw materials, and is suitable for large-scale production and application. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 This is a detailed synthetic route diagram of the novel photodegradable crosslinking agent Cou-AA in Example 1;
[0029] Figure 2 The novel photodegradable crosslinking agent Cou-AA in Example 1 1 H NMR;
[0030] Figure 3 The novel photodegradable crosslinking agent Cou-AA in Example 1 13 C NMR;
[0031] Figure 4 The mass spectrum of the novel photodegradable crosslinking agent Cou-AA in Example 1 is shown.
[0032] Figure 5 The image shows the basic photophysical properties of the novel photodegradable crosslinking agent Cou-AA in Example 2.
[0033] Figure 6 The diagrams show the preparation of photodegradable gels using the crosslinking agent Cou-AA and their photolithography in Examples 3-4.
[0034] Figure 7 These are gel imaging images obtained by photolithography using grating masks with linewidths of 75 mm and 100 mm, respectively, in Example 5.
[0035] Figure 8 The gel surface profile curves were obtained by photolithography using grating masks with linewidths of 75 mm and 100 mm, respectively, in Example 6.
[0036] Figure 9 The graphs show the relationship between etching depth and exposure time obtained by photolithography using grating masks with linewidths of 75 mm and 100 mm, respectively, in Example 6. Detailed Implementation
[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] A novel photodegradable crosslinking agent has the following chemical structural formula:
[0039]
[0040] The synthetic route of this novel photodegradable crosslinking agent (Cou-AA) is as follows: Figure 1 As shown, the specific preparation method includes the following steps:
[0041] S1, ethyl 4-chloroacetoacetate was added to methanesulfonic acid containing 4-bromo-m-diphenol, and after stirring, the reaction solution was cooled, allowed to stand to precipitate, filtered to obtain a solid, and then washed and dried to obtain compound 1;
[0042] S2, compound 1, K2CO3, and acrylic acid were dissolved in DMF (N,N-dimethylformamide), and the mixture was heated under anhydrous and oxygen-free conditions. After cooling to room temperature, compound 2 was obtained by extraction, drying, rotary evaporation, and purification.
[0043] S3, under a nitrogen protective atmosphere at 0℃, triethylamine and acryloyl chloride were added sequentially to an ultra-dry THF (tetrahydrofuran) solution containing compound 2 to carry out the reaction; after the reaction was completed, the solvent was evaporated and purified to obtain the crosslinking agent Cou-AA.
[0044] The applications of this novel photodegradable crosslinking agent are as follows:
[0045] This novel photodegradable crosslinking agent can undergo free radical polymerization with acrylic acid to form a three-dimensional crosslinked network structure, thus preparing a photodegradable gel. This gel can undergo photodegradation under light excitation of 250 nm to 350 nm.
[0046] The preparation steps of the photodegradable gel are as follows: acrylic acid, crosslinking agent Cou-AA and ammonium persulfate (APS) are dissolved in dimethyl sulfoxide and mixed evenly to obtain a transparent pregel solution. The mass of acrylic acid, Cou-AA and ammonium persulfate are 266 mg, 8 mg and 4 mg, respectively, and DMSO is 2 mL. The transparent pregel solution is injected into a polytetrafluoroethylene mold and polymerized at 73 °C for 1 h. The polymerized product is soaked in methanol for 4 h, which is the photodegradable gel prepared based on the novel photodegradable crosslinking agent.
[0047] Furthermore, with the aid of a photomask template, the photodegradable gel can be photoetched under light excitation of 250nm to 350nm.
[0048] The photolithography step is as follows: Photomasks with slit widths of 100mm and 75mm are placed under a 250nm–350nm xenon lamp light source (5.10mW / cm²). 2The photodegradable gel is placed between the photodegradable gel and the photodegradable gel, and exposed for 15 minutes to obtain an etched channel. After exposure, methanol is used to clean the gel to remove oligomer fragments generated by photolithography. The photodegradable gel is then placed in a 70°C forced-air drying oven to air dry for 12 hours, which is the etched gel.
[0049] The technical solution of the present invention will be described below through the following embodiments.
[0050] The sources of the raw materials used in the embodiments are shown in Table 1:
[0051] Table 1 List of raw materials in the embodiments
[0052]
[0053] The instruments used in the embodiments are shown in Table 2:
[0054] Table 2 List of instruments used in the embodiments
[0055]
[0056] Example 1
[0057] This embodiment provides a method for preparing a novel photodegradable crosslinking agent, Cou-AA, comprising the following steps:
[0058] (1) Preparation of compound 1: Ethyl 4-chloroacetoacetate (19.85 mmol) was added to methanesulfonic acid (20 mL) containing 4-bromo-m-diphenol (2.5 g, 13.22 mol) and stirred for 2 days; the reaction solution was introduced into ice water, allowed to stand and precipitate, filtered to retain the solid, washed with cold water and dried to obtain 2.5 g of grayish-white solid, with a yield of 89.3%.
[0059] Compound 1 1 H NMR is: 1 H NMR (400MHz, DMSO-d6)d (ppm): 11.57 (s, 1H), 8.00 (s, 1H), 6.92 (s, 1H), 6.48 (s, 1H), 5.01 (s, 2H).
[0060] (2) Preparation of Compound 2: Compound 1 (289.5 mg, 1 mmol) and K2CO3 (220.8 mg, 1.6 mmol) were placed in a reaction flask, and 8 mL of ultra-dry DMF and acrylic acid (115.2 mg, 1.6 mmol) were added. The reaction was carried out at 80 °C for 2 h under a nitrogen atmosphere. After cooling to room temperature, the mixture was washed with water and ethyl acetate, and the organic phase was retained. The mixture was dried over anhydrous sodium sulfate, and the solvent was evaporated. The mixture was purified by column chromatography with EA:PE = 1:6 (v / v) as the eluent. 177.4 mg of a white solid was obtained, with a yield of 54.6%.
[0061] Compound 2 1 The H NMR results are as follows: 1 H NMR(400MHz,DMSO-d6)d(ppm):11.56(s,1H),7.91(s,1H),6.91(s,1H),6.50- 6.41(m,1H),6.39-6.30(m,1H),6.23(s,1H),6.10-6.03(m,1H),5.44(s,2H).
[0062] Compound 2 13 The C NMR results are as follows: 13 C NMR (101MHz, DMSO-d6)d (ppm): 165.26, 160.05, 157.99, 154.29, 150.14, 133.34, 129.02, 128.06, 110.91, 109.50, 106.72, 103.66, 61.76.
[0063] The mass spectrometry results for compound 2 are as follows: MALDI-TOF-MS (m / z): calculated 325.114 for C 13 H9BrO5; found 325.270.
[0064] (3) Preparation of crosslinking agent Cou-AA: Under nitrogen atmosphere at 0℃, triethylamine (83.9 mL, 0.924 mmol) and acryloyl chloride (73.3 mL, 0.924 mmol) were added sequentially to an ultra-dry THF (5 mL) solution containing 2 (100 mg, 0.308 mmol), and the reaction was allowed to proceed overnight. The solvent was evaporated, and the solution was purified by column chromatography with EA:PE = 1:12 (v / v) as the eluent. 49.1 mg of a white solid was obtained, with a yield of 42.1%.
[0065] Crosslinking agent Cou-AA 1 The H NMR results are as follows Figure 2 As shown: 1 H NMR(400MHz,DMSO-d6)d(ppm):8.16(s,1H),7.66(s,1H),6.68-6.62(m,1H),6.55-6.45(m ,3H),6.39(d,J=10.2Hz,1H),6.28(d,J=10.4Hz,1H),6.08(d,J=10.4Hz,1H),5.52(s,2H).
[0066] Crosslinking agent Cou-AA 13 The C NMR results are as follows Figure 3 As shown: 13C NMR(101MHz,DMSO-d6)d(ppm):165.24,163.26,159.36,153.35,150.34,149.43, 135.78,133.39,129.25,128.05,127.12,117.19,113.46,113.32,111.76,61.74.
[0067] The mass spectrum of the crosslinking agent Cou-AA is as follows: Figure 4 As shown: MALDI-TOF-MS (m / z): calculated 379.162 for C 16 H 11 BrO6; found 380.459.
[0068] Example 2
[0069] In this embodiment, the crosslinking agent Cou-AA obtained in Example 1 was subjected to absorption and emission spectroscopy tests. The testing process included the following steps:
[0070] Prepare 10 using DMSO -3 Take 20 μL of the Cou-AA stock solution from M and dilute it to 2 mL with methanol to obtain the test sample with a concentration of 10. -5 M; The absorption spectrum of the sample was measured using a Shimadzu UV-2600 UV-Vis spectrophotometer, and the emission spectrum was measured using a Hitachi F-7000 fluorescence spectrophotometer with an excitation wavelength of 327 nm.
[0071] Test results are as follows Figure 5 As shown, Figure 5 In this context, 'a' represents a methanol solution of the crosslinking agent Cou-AA (10... -5 The absorption spectrum of M at 298 K; Figure 5 In this context, b represents a methanol solution of the crosslinking agent Cou-AA (10). -5 The emission spectrum of M) at 298K shows that Cou-AA exhibits strong absorption in the range of 250 nm to 350 nm, with the maximum absorption peak located at 326 nm. The calculated extinction coefficient (e) at this absorption peak is 6.37 × 10⁻⁶. 3 M -1 cm -1 Cou-AA exhibits strong blue light emission in the 430nm–520nm range, with the maximum emission peak located at 473nm.
[0072] Example 3
[0073] This embodiment describes a method for preparing a photodegradable gel based on a novel photodegradable crosslinking agent, comprising the following steps:
[0074] Cou-AA (8 mg), acrylic acid (280 mL), and ammonium persulfate (APS, 4 mg) were dissolved in DMSO (2 mL) and mixed thoroughly to obtain a transparent pregel solution. The solution was then injected into a polytetrafluoroethylene mold and polymerized at 73 °C for 1 hour. The polymer product was then soaked in methanol for 4 hours to obtain the photodegradable gel.
[0075] The schematic diagram of the photolysis process of the Cou-AA crosslinking agent in the hydrogel and the photolithography of the hydrogel using a mask is shown below. Figure 6 As shown.
[0076] Example 4
[0077] In this embodiment, the photodegradable gel obtained in Example 3 is subjected to photolithography, including the following steps: placing a photomask with slit widths of 100 mm and 75 mm on a xenon lamp light source (5.10 mW / cm²) equipped with a 320 nm bandpass filter. 2 The gel was exposed to the gel for 5 min, 10 min, 15 min, and 25 min to obtain an etched channel. After exposure, methanol was used to clean the gel and remove the oligomer fragments generated by photolithography. The gel was then placed in a 70℃ forced-air drying oven and dried for 12 h to obtain the photolithographically etched gel.
[0078] Example 5
[0079] In this embodiment, the photo-etched gel obtained in Example 4 was used as a test sample. The photo-etched channel was observed and imaged using a Zeiss Primotech optical microscope.
[0080] The results are as follows Figure 7 As shown, it can be seen that after photolithography, a series of parallel etching channels are obtained, and the channel width is consistent with the slit width of the photomask used, thus achieving precise etching.
[0081] Example 6
[0082] In this embodiment, the photo-etched gel obtained in Example 4 was used as a test sample, and the contour curve of the photo-etched channel was tested using a Bruker Dektak XT profilometer.
[0083] The results are as follows Figure 8 and Figure 9 As shown, where, Figure 8 In the figure, 'a' represents the gel surface profile obtained by photolithography using a 100mm linewidth grating mask. Figure 8 In the figure, b represents the gel surface profile obtained by photolithography using a 75mm linewidth grating mask; from Figure 8 and Figure 9As can be seen, depressions appear in the exposed areas, and the depth of these depressions increases with prolonged exposure time. When the slit width of the photomask is 100 μm, the etching rate is faster and the etching depth is deeper than when using a photomask with a slit width of 75 μm. This may be because, with a slit width of 75 μm, the photolytically crosslinking agent exposed to the light is more dispersed, making it difficult to form oligomer fragments that can be washed away by solvents, thus reducing the etching depth. This demonstrates that the etching width has a significant impact on the etching depth.
[0084] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0085] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A photodegradable crosslinking agent, characterized in that, The structural formula is:
2. The method for preparing a photodegradable crosslinking agent according to claim 1, characterized in that, Includes the following steps: S1, ethyl 4-chloroacetoacetate was added to methanesulfonic acid containing 4-bromo-m-diphenol, and after stirring, the reaction solution was cooled, allowed to stand to precipitate, filtered to obtain a solid, and then washed and dried to obtain compound 1; S2, compound 1, K2CO3 and acrylic acid were dissolved in DMF, heated to react, then cooled to room temperature, and after extraction, drying, rotary evaporation and purification, compound 2 was obtained; S3, under a nitrogen atmosphere, triethylamine and acryloyl chloride are added sequentially to an ultra-dry THF solution containing compound 2 to carry out the reaction; after the reaction is completed, the solvent is evaporated and purified to obtain the photolytic crosslinking agent.
3. The method for preparing a photodegradable crosslinking agent according to claim 2, characterized in that, The synthetic route for photodegradable crosslinking agents is as follows:
4. The method for preparing a photodegradable crosslinking agent according to claim 3, characterized in that, In S2, the heating reaction is carried out under anhydrous and oxygen-free conditions.
5. The application of the photodegradable crosslinking agent according to claim 1 in the preparation of photodegradable gels.
6. A method for preparing a photodegradable gel, characterized in that, Includes the following steps: Acrylic acid, the photodegradable crosslinking agent according to claim 1, and ammonium persulfate are dissolved in dimethyl sulfoxide and mixed evenly to obtain a pregel solution; After polymerizing the pregel solution, it is immersed in methanol to obtain a photodegradable gel.
7. The method for preparing a photodegradable gel according to claim 6, characterized in that, The mass ratio of acrylic acid, photodegradable crosslinking agent, and ammonium persulfate is 133:4:
2.
8. The method for preparing a photodegradable gel according to claim 6, characterized in that, The polymerization temperature is 73°C.
9. A photolytically degradable gel, characterized in that, Prepared using the preparation method according to any one of claims 6-8.
10. The application of the photodegradable gel according to claim 9 in the preparation of microfluidic chips and drug carriers.